Influence of ZnO and TiO2 nanoparticles in the establishment and growth of in vitro callus cultures of coﬀee - Devasia, Jeena; Muniswamy, B.; Jingade, Pavankumar; Huded, Arun Kumar C.; Mishra, M. K. (Journal of Plantation Crops, 2023)
-